Der lange Atem kolonialer Bilder Visuelle Praktiken von (Ex-)Soldaten und ihren Familien in Südtirol/Alto Adige 1935-2015 - Wurzer, Markus (Wallstein Verlag, 2023)
Colonialism is part of many European family histories. Photographs convey collective ideas about the colonial past. This book explores how and for what purpose colonial images were (re-)produced, used, and passed on through generations by soldiers and their families.